2022
DOI: 10.1155/2022/3335048
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Prediction Value of Pelvic Lymph Node Metastasis of Endometrial Cancer: Combining of ADC Value and Radiomics Features of the Primary Lesion and Clinical Parameters

Abstract: Objective. To investigate the value of apparent diffusion coefficient (ADC) value of endometrial cancer (EC) primary lesion and magnetic resonance imaging (MRI) three-dimensional (3D) radiomics features combined with clinical parameters for preoperative prediction of pelvic lymph node metastasis (PLNM). Methods. A total of 136 patients with EC confirmed by postoperative pathology were retrospectively reviewed and analyzed. Patients were randomly divided into training set (n = 95) and test set (n = 41) at a rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…Among them, 11 studies ( 21 , 30 , 31 , 33 , 36 , 45 , 55 , 61 63 , 65 ) adopted the method of external validation, and the remaining studies carried out internal validation by random sampling. Nine studies ( 20 22 , 31 , 32 , 35 , 45 , 52 ) did not clearly describe the variable screening method and mainly adopted single-factor and multi-factor logistic regression.…”
Section: Resultsmentioning
confidence: 99%
“…Among them, 11 studies ( 21 , 30 , 31 , 33 , 36 , 45 , 55 , 61 63 , 65 ) adopted the method of external validation, and the remaining studies carried out internal validation by random sampling. Nine studies ( 20 22 , 31 , 32 , 35 , 45 , 52 ) did not clearly describe the variable screening method and mainly adopted single-factor and multi-factor logistic regression.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies have shown that such a two-step strategy combining preoperative histopathologic evaluation with ultrasound evaluation of myometrial and cervical stroma invasion helps identify cases at high and low risk of lymph node metastasis with a sensitivity and specificity of 83% and 71%, respectively [ 44 , 45 ].…”
Section: Imaging In Metastasismentioning
confidence: 99%
“…Federation of Gynecology and Obstetrics (FIGO) stage, serum cancer antigen 125 (CA-125) and human epididymis protein 4 (HE4), and histologic molecular markers have been investigated and analyzed in the diagnosis and prognosis of EC patients [7][8][9][10]. Meanwhile, 18F-fluorodeoxyglucose ( 18 F-FDG) PET/computed tomography (CT) combines morphological and physiologic imaging techniques and is widely used for diagnosis, staging and prognosis of various cancers.…”
Section: Many Clinicopathological Factors Including Internationalmentioning
confidence: 99%
“…This may be because of different histological types and sample sizes. Ki-67 is a marker of cell proliferation, suggesting that higher Ki-67 index, higher proliferative activity, stronger invasiveness, and higher cell density [7]. 18 F-FDG PET/CT metabolic parameters had been proven to play an important role in identifying tumors with high proliferation and aggressive behavior in clinical practice.…”
Section: Figmentioning
confidence: 99%